Prevalence of antibodies targeting ubiquitin-conjugating enzyme 2L3 and eukaryote translation elongation factor 1 α1 in Chinese Han and American Caucasian populations with type 1 diabetes. Issue 12 (23rd November 2022) - Qian, Li; Zhu, Yuxiao; Luo, Yan; Zhang, Mu; Yu, Liping; Liu, Yu; Yang, Tao
Abstract : We assessed the prevalence of two novel islet autoantibodies, those targeting ubiquitin-conjugating enzyme 2L3 (UBE2L3) and eukaryote translation elongation factor 1 α1 (eEF1A1), in type 1 diabetes mellitus (T1DM) to evaluate their utility in T1DM diagnosis with comparison to other islet autoantibodies. We also aimed to determine whether age and ethnicity impacted their diagnostic value. Electrochemiluminescence assay was used to detect UBE2L3-Ab and eEF1A1-Ab in 193 Chinese Han and 570 American Caucasian subjects with T1DM, and 282 Chinese Han and 199 American Caucasian controls. In Chinese and American cohorts, the UBE2L3-Ab cut-off indices were 0.039 and 0.038, and the eEF1A1-Ab cut-off indices were 0.048 and 0.050, respectively. The prevalence of UBE2L3-Ab was significantly higher in the Chinese (9.33%) and American (3.86%) subjects with T1DM than in the controls ( P < 0.05). The prevalence of UBE2L3-Ab in T1DM was significantly higher in Chinese than in American ( P < 0.05). Albeit not statistically significant, the prevalence of UBE2L3-Ab in T1DM was slightly higher in children than in adults of both ethnicities. The differences in eEF1A1-Ab levels between subjects with T1DM and controls were not significant. Meanwhile, all American subjects with UBE2L3-Ab also harbored glutamic acid decarboxylase autoantibody (GADA) or insulin autoantibody (IAA). In contrast, 2.07% of the Chinese subjects with UBE2L3-Ab positive were previously classiﬁed as autoantibody-negative based on GADA and IAA. So the prevalence of UBE2L3-Ab in T1DM patients was significantly higher than in controls and was variable according to ethnicity as well as tended to be higher in children than adults. However, UBE2L3-Ab and eEF1A1-Ab may not be reliable diagnostic biomarkers forT1DM.